The Effect of Halal Tourism and Behavioural Intention on Revisit Intention - Setyawan, Febri Fajar; Mardalis, Ahmad (Jurnal Ilmiah Poli Bisnis, 2023)
This study aims to determine the effect of halal tourism, behavioral intention on revisit intention. To determine the effect of halal tourism, behavioral intention on tourist satisfaction. To find out tourist satisfaction on revisit intention and to find out the effect of tourist satisfaction mediating the relationship between halal tourism and behavioral intention on revisit intention. The population in this study were tourists visiting the city of Surakarta, while the sample was 200 responden using the sampling technique, namely non-probability sampling using purposive sampling and the data collection method using online questionnaires with the help of the Google form facility. The results of the data analysis obtained that the halal tourism variable has a positive and significant effect on revisit intention. The result of the behavioral intention variable have a significant effect on revisit intention. The results of the halal tourism variable have a positive and significant effect on tourist satisfaction. The results of the behavioral intention variable have a positive and significant effect on tourist satisfaction. The results of the mediation show that tourist satisfaction can mediate positively and significantly between halal tourism and revisit intention, as evidenced by the statistical t value. The results of the mediation show that tourist satisfaction can mediate positively and significantly between behavioral intention and revisit intention.